2015
DOI: 10.3892/mmr.2015.4088
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of zinc on the advanced glycation end product-induced apoptosis of mouse osteoblastic cells

Abstract: Osteoporosis and diabetes have become serious health problems worldwide. Previous studies have suggested that diabetes is associated with osteoporosis and increased fracture risk. However, the mechanism underlying diabetes‑induced osteoporosis remains to be elucidated. Therefore, the present study aimed to examine the mechanism underlying diabetes‑induced osteoporosis, and determine the protective effects of zinc, which is known to be closely associated with osteoporosis and diabetes. The results of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The increased production of ROS contributes to the release of Cyto-C from mitochondria into the cytosol (Liang et al, 2012), which facilitates cell apoptosis and osteoporosis (Xiong et al, 2015). Activation of NF-κB contributes to mitochondrial dysfunction, which further potentiates NF-κB activation (Cherry and Piantadosi, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The increased production of ROS contributes to the release of Cyto-C from mitochondria into the cytosol (Liang et al, 2012), which facilitates cell apoptosis and osteoporosis (Xiong et al, 2015). Activation of NF-κB contributes to mitochondrial dysfunction, which further potentiates NF-κB activation (Cherry and Piantadosi, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Zinc administration significantly decreased this effect. Xiong et al assessed protective effects of zinc against AGE‑induced apoptosis and ROS generation. The authors reported that AGEs induce cell apoptosis and increase cellular ROS levels and suppress cell growth and viability, whereas, zinc administration prevents AGE‐induced cell apoptosis and the creation of ROS and improves cell viability.…”
Section: Effect Of Zinc Supplementation On Age Generation and Age‐indmentioning
confidence: 99%
“…Activation of survival signalling pathways, mitogen‐activated protein kinase/extracellular signal‐regulated kinase and phosphoinositide 3‐kinase/AKT signalling pathways, have been implicated to trigger anti‑apoptotic signal transduction pathways and to inhibit caspase‐3 formation/activity and delay of apoptosis, through ERK and Akt . Treatment with zinc substantially up regulates the expression levels of p‑ERK and p‑AKT in AGE‑treated cells and effectively protects the cells from AGE‑induced apoptosis …”
Section: Possible Mechanistic Model Of Zinc In the Inhibition Of Age‐mentioning
confidence: 99%
See 2 more Smart Citations